Body mass index, comorbid conditions, and demographic factors among tertiary healthcare workers in Kosovo: Implications for physical activity interventions - Hoti, Flaka; Shehu Kaqi, Merlinda; Terziqi, Hasime; Shehu, Myhidin (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to determine the prevalence of overweightness and obesity among healthcare workers (HCWs) at the University Clinical Center of Kosovo in Pristina, Kosovo, and to examine the relationship between demographic variables, comorbid conditions, and body mass index (BMI). This was a retrospective, descriptive, analytical study. The study population consisted of 3048 HCWs at the University Clinical Center of Kosovo in Pristina, Kosovo. The sample consisted of all HCWs who were willing to provide his/her BMI (n = 1399) and included 717 females (51.25%) and 682 males (48.75%) with an average age of 48.16±10.46 years. Biochemical and hematological tests were carried out. BMI and blood pressure were assessed. The prevalence of overweight and obesity class I was 49.1% and 19.8%, respectively, according to WHO criteria, where overweight is defined as BMI 25.0–29.9 and obesity class I as BMI 30.0–34.9. Males were found to have a higher mean BMI compared to females (p=0.01). Hypertension, dyslipidemia, and hyperglycemia were found to be statistically significant with BMI (p<0.01) while type II diabetes was insignificant (p=0.05). Age was associated with type II diabetes (p<0.05) and hypertension (p=0.05); sex was significantly associated only with hyperglycemia (p<0.05). With an increase in age for both sexes, the rates of obesity and overweight increased, especially from ages 45 to 54 in HCWs. BMI was a significant predictor of hypertension (p<0.01, OR=1.45), dyslipidemia (p<0.01, OR=1.42), and hyperglycemia (p<0.01, OR=1.48). These results indicate the need for increased physical activity in order to reverse obesity-related health problems and obtain better health among HCWs.